Time for nutrition in medical education. Issue 1 (16th April 2020) - Macaninch, Elaine; Buckner, Luke; Amin, Preya; Broadley, Iain; Crocombe, Dominic; Herath, Duleni; Jaffee, Ally; Carter, Harrison; Golubic, Rajna; Rajput-Ray, Minha; Martyn, Kathy; Ray, Sumantra
Abstract : Aim: To synthesise a selection of UK medical students' and doctors' views surrounding nutrition in medical education and practice. Methods: Information was gathered from surveys of medical students and doctors identified between 2015 and 2018 and an evaluation of nutrition teaching in a single UK medical school. Comparative analysis of the findings was undertaken to answer three questions: the perceived importance of nutrition in medical education and practice, adequacy of nutrition training, and confidence in current nutrition knowledge and skills. Results: We pooled five heterogeneous sources of information, representing 853 participants. Most agreed on the importance of nutrition in health (>90%) and in a doctor's role in nutritional care (>95%). However, there was less desire for more nutrition education in doctors (85%) and in medical students (68%). Most felt their nutrition training was inadequate, with >70% reporting less than 2 hours. There was a preference for face-to-face rather than online training. At one medical school, nutrition was included in only one module, but this increased to eight modules following an increased nutrition focus. When medical students were asked about confidence in their nutrition knowledge and on advising patients, there was an even split between agree and disagree (p=0.869 and p=0.167, respectively), yet few were confident in the UK dietary guidelines. Only 26% of doctors were confident in their nutrition knowledge and 74% gave nutritional advice less than once a month, citing lack of knowledge (75%), time (64%) and confidence (62%) as the main barriers. There was some recognition of the importance of a collaborative approach, yet 28% of doctors preferred to get specialist advice rather than address nutrition themselves. Conclusion: There is a desire and a need for more nutrition within medical education, as well as a need for greater clarity of a doctor's role in nutritional care and when to refer for specialist advice. Despite potential selection bias and limitations in the sampling frame, this synthesis provides a multifaceted snapshot via a large number of insights from different levels of training through medical students to doctors from which further research can be developed.